PERAN MARKETPLACE TERHADAP PENINGKATAN PENDAPATAN UMKM DI KOTA MATARAM - Ida Bagus Ariawan; Muhammad Nur Abdi (Universitas Muhammadiyah Luwuk Banggai, 2023)
Marketplace is a place to market products electronically by bringing together sellers and buyers to interact with each other. Sales carried out by business actors is an activity that must run well, because with good sales, business income will increase. Good sales are accompanied by a conceptualized marketing strategy, this is so that the strategy created has an impact on reaching the target market. The role of technology is needed by business actors, because nowadays everything is side by side with technology. Several MSMEs in Mataram City utilize marketplace technology in marketing their products and supporting increased sales in terms of online. In this study using qualitative methods by conducting interviews. The purpose of this study was to determine the role of marketplace in increasing the income of MSMEs in Mataram City. The number of participants was 11 informants from MSMEs business actors in Mataram City. The results showed that there was a role of the marketplace in increasing revenue for MSMEs as seen from the good and positive assessment by informants. Based on the results of this study, according to MSME business actors, the marketplace is considered important and useful so that the platform needs to be used by MSMEs to increase their income.